The online advertising playbook proven strategies and tested tactics from the Advertising Research Foundation - Plummer, Joseph Thornton 1941- (John Wiley & Sons, 2007)
"The Advertising Research Foundation's Online Advertising Playbook is the new benchmark for best practices. It relies on data, not guesswork, to explain what's working and not working on the Internet, and answers all the most vital questions advertisers have about online marketing." "This book synthesizes research and learning from over 1,200 research documents on Internet advertising. Marketers, brand managers, and agency professionals who need actionable, scientifically solid principles for successful advertising in this new medium will find it in the Playbook."--Jacket
Includes bibliographical references (pages 265-289) and index. - Print version record
Keywords: Internet advertising; Publicité sur Internet; BUSINESS & ECONOMICS; Advertising & Promotion